1982
DOI: 10.1159/000182802
|View full text |Cite
|
Sign up to set email alerts
|

Serum Aluminum Levels in Dialysis Dementia

Abstract: Serum aluminum concentrations were measured in 7 normal persons, 47 chronic hemodialysis patients and in 10 patients with the dialysis dementia syndrome. The concentrations were (mean ± 1 SEM): 35 ± 3.7, 109.3 ± 10.6, and 369 ± 51.6 µg/l, respectively. These results are consistent with the theory that aluminum is involved in the pathogenesis of this syndrome. In contrast to most previous reports dialysate contaminated with aluminum could not be implicated in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…However, excess or defi ciency of trace elements, which was disregarded until several years ago, has recently been noticed as one of the factors that induce complications in dialyzed patients. In 1972, Alfrey et al [1] reported cases of dialysis dementia possibly due to aluminum intoxication [2], A number of observations indicate a high aluminum concentration in plasma, which may accelerate dialysis dementia and re nal osteodystrophy [3][4][5][6]. In the plasma of dialyzed pa tients, zinc concentration is decreased [7,8], and copper concentration increased [7,9].…”
mentioning
confidence: 99%
“…However, excess or defi ciency of trace elements, which was disregarded until several years ago, has recently been noticed as one of the factors that induce complications in dialyzed patients. In 1972, Alfrey et al [1] reported cases of dialysis dementia possibly due to aluminum intoxication [2], A number of observations indicate a high aluminum concentration in plasma, which may accelerate dialysis dementia and re nal osteodystrophy [3][4][5][6]. In the plasma of dialyzed pa tients, zinc concentration is decreased [7,8], and copper concentration increased [7,9].…”
mentioning
confidence: 99%
“…In the 1980s, a progressively more extensive use of reverse osmosis for dialysis water treatment markedly reduced aluminum levels in the dialysate, with a large reduction in the incidence of dialysis dementia (7). However, it should be kept in mind that in some cases aluminum present in phosphate binders has been found to induce osteomalacia and encephalopathy by accumulation in bone and cerebral tissues (8).…”
Section: Dialysis Dementiamentioning
confidence: 99%
“…Serum aluminum concentrations [17] and grey matter aluminum content [18] have been shown to be higher in patients with dialysis encephalopathy than in uremic patients on hemodialysis without neurological symptoms and in nonuremic controls. Ladurneret al [19] concluded from a study of 64 dialysis patients that there is a direct correlation between serum aluminum concentrations and the appearance of dementia as well as electroencephalographic changes.…”
Section: Clinical and Pathophysiologic Featuresmentioning
confidence: 99%